2012
DOI: 10.1146/annurev-psych-120710-100431
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Automatized Naming (RAN) and Reading Fluency: Implications for Understanding and Treatment of Reading Disabilities

Abstract: Fluent reading depends on a complex set of cognitive processes that must work together in perfect concert. Rapid automatized naming (RAN) tasks provide insight into this system, acting as a microcosm of the processes involved in reading. In this review, we examine both RAN and reading fluency and how each has shaped our understanding of reading disabilities. We explore the research that led to our current understanding of the relationships between RAN and reading and what makes RAN unique as a cognitive measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

54
582
1
28

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 601 publications
(665 citation statements)
references
References 96 publications
(93 reference statements)
54
582
1
28
Order By: Relevance
“…A third possibility is that the link between phonological processes and beat synchronization is restricted to phonological awareness. Perhaps rapid automatized naming, which is dissociable from phonological awareness and makes an independent contribution to reading skill (89), relies on precise perception of auditory timing to a lesser extent than does phonological awareness.…”
Section: Discussionmentioning
confidence: 99%
“…A third possibility is that the link between phonological processes and beat synchronization is restricted to phonological awareness. Perhaps rapid automatized naming, which is dissociable from phonological awareness and makes an independent contribution to reading skill (89), relies on precise perception of auditory timing to a lesser extent than does phonological awareness.…”
Section: Discussionmentioning
confidence: 99%
“…While RAN and reading require many of the same processes, particularly the connecting of orthographic and phonological representations (Norton & Wolf, 2012), the former is considered a universal predictor of reading fluency across all known orthographies (Georgiou, Parrila, & Papadopoulos, 2008).…”
Section: The Key Role Of Phonological Processing and Morphological Awmentioning
confidence: 99%
“…Since the seminal work of Denckla and Rudel (1976), a large body of research has demonstrated a strong relationship between rapid automatized naming (RAN) and both concurrent and future literacy skills (see Kirby, Georgiou, Martinussen, &Parrila, 2010, andNorton &Wolf, 2012, for reviews). This relationship has been shown in practically every language in which it has been tested, including Portuguese (e.g., Albuquerque, 2012;Justi & Roazzi, 2012), and regardless of variations in other predictors of literacy ability, such as verbal and non-verbal skills, general processing speed, and phonological awareness (Kirby et al, 2010).…”
mentioning
confidence: 99%